Behavior of Generation Z Is Revie Swed from the Perspective of Islamic Economics - Nur Sakinah; Dian Martha Darman; Lita Arfah; Marro’aini Marro’aini; Indra Kurniawan (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
This study aims to analyze the phenomenon of Fear of Missing Out (FOMO) in Generation Z's online shopping behavior and review it from the perspective of Islamic Economics. This study uses a qualitative descriptive approach with data collection techniques through interviews, observations, and documentation involving Generation Z individuals who actively shop online. Data is analyzed through the stages of data reduction, data presentation, and conclusion drawn. The results show that FOMO influences online shopping behavior through the desire to follow trends, buy products that are currently viral, respond to influencer recommendations, and take advantage of digital promotions such as flash sales and limited-time discounts. These factors often drive impulse purchases without considering the actual needs. From the perspective of Islamic Economics, consumption behavior driven by FOMO has the potential to cause excessive attitudes and waste if not accompanied by self-control. Therefore, the principles of benefit, moderation, and responsibility in asset management are important guidelines in directing online shopping behavior